Analysis on strength, weaknesses, and challenges in Chemistry Learning Course: a descriptive study to enhance the quality of learning. Issue 4 (February 2019) - Allo, E L; Permanasari, A; Wiji, W; Redjeki, S
Abstract: Chemistry Instructional Planning (CIP) is one of courses provided by most of Chemistry Education Department as a part of Chemistry Education curriculum. The course aims to enhance chemistry prospective teachers' capabilities in designing lesson plan (LP). Descriptive study was conducted to explore the strength, and weaknesses of CIP curriculum and its implementation. The results were expected to contribute in improving the quality of CIP course (CIPc). The objects of this research were secondary data curriculum, LP made by student, and learning situation. The research instruments were curriculum assessment format, assessment rubric of LP and class observation sheet. The result shows that some strengths were found in the curriculum and implementation of the CIPc. In general, the course has facilitated students to design learning step by step. However, the weakness that must be anticipated was learning process has not trained the metacognition skills. This skills are needed in designing LP to exercise argumentation, and reflecting skills. Therefore, reorientation of CIPc and learning is recommended to fit with expectation.